A Mega-Ethnography of Qualitative Meta-Syntheses on Return to Work in People with Chronic Health Conditions - Schwarz, Betje; Banaschak, Hannes; Heyme, Rebekka; von Kardorff, Ernst; Reims, Nancy; Streibelt, Marco; Bethge, Matthias (Die Rehabilitation, 2023)
Purpose The aim of this study was to synthesize the findings of qualitative meta-syntheses (QMS) on return to work (RTW) of people with different chronic illnesses and to develop a generic RTW model that can provide advice on how to improve RTW interventions and strategies.Methods We conducted a systematic literature search in PubMed, Epistemonikos, CENTRAL, and PsycARTICLES to find relevant QMS, published in English or German between 2000 and 2021, and adapted the meta-ethnographic approach of Noblit and Hare to synthesize their findings.Results Nineteen QMS (five focusing on musculoskeletal disorders or chronic pain, four on acquired or traumatic brain injuries, four on cancer, two on mental disorders, one on spinal cord injury, and three on mixed samples) met our inclusion criteria for the meta-ethnographic synthesis. Through systematic comparison and reciprocal translation of the single QMS findings, we could identify a set of key cross-cutting themes/concepts, which formed the basis for four RTW principles and a generic RTW model.Conclusions RTW is a multifactorial and highly interactive multistakeholder process, embedded in an individual‘s life and working history, as well as in a determined social and societal context. It runs parallel and interdependently to the process of coping with the disease and realigning one’s own identity, thus emphasizing the significance of RTW for the person. Besides symptoms and consequences of the disease, individual coping strategies, and RTW motivation, the course and success of RTW are strongly affected by the adaptability of the person’s working environment and the social support in their private and working life. Thus, RTW is not only a problem of the individual, but also a matter of the social environment, especially the workplace, requiring a holistic, person-centered, and systemic approach, coordinated by a designated body, which considers the interests of all actors involved in the RTW process.
Keywords: review; meta-synthesis; return to work; mega-ethnography; qualitative evidence synthesis; chronic illnesses